Treatment of distal clavicle fracture of Neer type II with locking plate in combination with titanium cable under the guide - Jun Wang (Nature Portfolio, 2021)
Abstract To observe and compare the curative effect of a locking plate plus titanium cable under the Guide device and clavicular hook plate in the treatment of Neer type II distal clavicle fractures. A prospective cohort study was conducted to analyse the clinical data of 36 patients with distal clavicle fractures from January 2016 to January 2019. The results were analysed. According to the random number method, the patients were divided into two groups: the titanium cable group (fixed with a titanium cable in combination with a locking plate) and hook plate group (fixed with a clavicular hook plate only). Under the guidance of a special device (for which a patent was obtained), in the titanium cable group, the coracoclavicular ligament was fixed with tension reduction, and then the distal clavicular fracture was fixed with a locking plate. In the hook plate group, the distal clavicle fracture was fixed with a hook plate. The incision length, operation time, bleeding volume and VAS score before, 1 week after and 1 year after the operation were compared between the two groups. The effect of the operation was evaluated by the Constant-Murley score before and 1 year after the operation. X-ray films were taken 2 days, 3 months, half a year and 1 year after the operation to observe the reduction and healing of fractures. At the same time, complications were recorded. The amount of bleeding was the same in the two groups. The operation time in the hook plate group was relatively short, and the difference was statistically significant (P < 0.05). The VAS score in the titanium cable group was significantly lower than that in the hook plate group one year after the operation. The Constant-Murley score in the titanium cable group and hook plate group was significantly higher 1 year after the operation. The number of postoperative complications in the titanium cable group was significantly lower than that in the hook plate group. The treatment of Neer type II distal clavicle fractures with a titanium cable plus a locking plate has a good curative effect, few complications and good postoperative recovery and thus is worth popularizing.